(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article discusses the use of artificial intelligence in education, as well as solving the problems of personalization of education and career guidance. Identified and analyzed the need for the introduction of artificial intelligence in the learning process, as well as technologies that are already in use. The possibilities of using artificial intelligence in the personalization of learning are presented. After analyzing the possibilities of using artificial intelligence, we came to the conclusion that it is necessary to use and improve the technologies of neural networks and artificial intelligence in education.